2021
DOI: 10.3390/jpm11050374
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Maturated Early-Stage Human-Induced Pluripotent Stem Cell-Derived Cardiomyocytes Improve Cardiac Function by Enhancing Segmental Contraction in Infarcted Rats

Abstract: The scant ability of cardiomyocytes to proliferate makes heart regeneration one of the biggest challenges of science. Current therapies do not contemplate heart re-muscularization. In this scenario, stem cell-based approaches have been proposed to overcome this lack of regeneration. We hypothesize that early-stage hiPSC-derived cardiomyocytes (hiPSC-CMs) could enhance the cardiac function of rats after myocardial infarction (MI). Animals were subjected to the permanent occlusion of the left ventricle (LV) ante… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 76 publications
(179 reference statements)
0
14
0
Order By: Relevance
“…The miRNAs exhibiting Profile 1 when overexpressed delayed maturation characteristics mainly associated with structural changes, whereas miR-124-3p regulated both structural and functional features. Altogether, we (1) identified a molecular signature for tracking in vitro cardiac differentiation over time; (2) provided evidence that the miRNA/gene pairs display biological relevance; and (3) showed that most of the top-scoring miRNAs influence the proliferation-maturation axis. The improved understanding of the interplay among miRNAs and gene targets may be instrumental in developing more robust human cardiac disease modeling systems and cardiac cell-based regenerative approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The miRNAs exhibiting Profile 1 when overexpressed delayed maturation characteristics mainly associated with structural changes, whereas miR-124-3p regulated both structural and functional features. Altogether, we (1) identified a molecular signature for tracking in vitro cardiac differentiation over time; (2) provided evidence that the miRNA/gene pairs display biological relevance; and (3) showed that most of the top-scoring miRNAs influence the proliferation-maturation axis. The improved understanding of the interplay among miRNAs and gene targets may be instrumental in developing more robust human cardiac disease modeling systems and cardiac cell-based regenerative approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) are instrumental for the complete development of cardiac disease cell-modeling systems, patient-specific drug tests, and strategies to replace lost cardiomyocytes [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, the iPSC-CMs generation, thanks to the improvement of differentiation and purification techniques, has opened the door for clinical applications. The underlying mechanism of MI and the therapeutic effect of iPSC-CMs have been demonstrated in several small and large animal models of MI, such as mice [ 118 , 119 ], rats [ 120 , 121 ], and pigs [ 121 , 122 , 123 ]. A significant study published by Chong et al regarding the use of ESC-CMs in a non-human-primate model (pigtail macaque) of myocardial ischemia-reperfusion resulted in remuscularization of heart tissue but incomplete cell maturation [ 50 ].…”
Section: Cell-based Therapies For MImentioning
confidence: 99%
“…Article [14] signifies that the meager capacity to remodel makes heart recovery one of the greatest difficulties. Current treatments don't think about heart re-muscularization.…”
Section: Literature Reviewmentioning
confidence: 99%